Enhancing Circular Waste Management Behavior Through Adaptive Capacity With Structural Equation Modeling Framework in Bali, Indonesia - I Wayan Koko Suryawan; Ari Rahman; Mega Mutiara Sari (Tecno Scientifica Publishing, 2026)
This research examined the intricacies of circular waste management behaviors in Bali, Indonesia, using a Structural Equation Modeling (SEM) framework focused on adaptive capacity. Adaptive capacity was defined through five key dimensions: assets, flexibility, organization, learning, and agency. These elements were critical in shaping the intentions and behaviors associated with sustainable waste management practices. The study systematically explored how these interconnected dimensions of adaptive capacity either facilitated or impeded the adoption of practices aligned with the principles of the circular economy. The SEM approach was employed to map and validate the relationships between the dimensions of adaptive capacity and their impact on waste management behaviors. This analytical method provided a robust framework for understanding the complex dynamics at play, highlighting how different facets of adaptive capacity interacted to influence sustainable practices. Key findings underscored the critical role of individual empowerment, the effectiveness of organizational structures, and the impact of educational initiatives in driving sustainable waste management behaviors. These insights suggested that enhancing individual agency, optimizing organizational protocols, and expanding learning opportunities were pivotal in fostering more sustainable waste management practices.